2008
DOI: 10.1097/mca.0b013e3282fd5c4e
|View full text |Cite
|
Sign up to set email alerts
|

Increased peripheral circulating inflammatory cells and plasma inflammatory markers in patients with variant angina

Abstract: Taken together, these findings suggested that more chronic, severe inflammation might be involved in the pathogenesis of VA, manifested by increased counts of circulating inflammatory cells and elevated plasma levels of CRP and IL-6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…These findings were consistent with the hypothesis that endothelial dysfunction in this setting may be attributable to a state of systemic inflammation. Recently clinical reports also suggested that systemic inflammatory activity is increased in patients with VA [23][24][25][26]. In our study, the levels of WBC and monocyte cell counts were significantly higher in patients of the VA group than in the other two groups.…”
Section: Figuresupporting
confidence: 58%
“…These findings were consistent with the hypothesis that endothelial dysfunction in this setting may be attributable to a state of systemic inflammation. Recently clinical reports also suggested that systemic inflammatory activity is increased in patients with VA [23][24][25][26]. In our study, the levels of WBC and monocyte cell counts were significantly higher in patients of the VA group than in the other two groups.…”
Section: Figuresupporting
confidence: 58%
“…A recent study by Hung et al, (2006) [91] has further shown that IL-6 levels were independently associated with the diagnosis of coronary vasospastic angina pectoris in the absence of advanced CAD supporting the hypothesis that coronary vasospasm at least in part represent an inflammatory condition. In addition, Li et al [92] recently reported that patients with variant angina display higher white blood cell and monocyte cell counts. Similarly, plasma IL-6 and CRP levels in that study were higher in variant angina patients compared with those patients with stable CAD.…”
Section: Vasospasm and Myocardial Infarctionmentioning
confidence: 99%
“…Additionally, a recent study has suggested a strong association between circulating IL-6 levels and CHD risk in two population-based cohort studies along with a systematic review [41]. Another study showed that plasma IL-6 and CRP levels were higher in variant angina patients compared with those patients with stable CAD [42]. Similarly, significantly elevated circulating plasma levels of IL-6 and IL-6R (α and β) have been observed in patients with acute myocardial infarction.…”
Section: Interleukin-6mentioning
confidence: 94%